The revival of the anti-Ottoman projects in the Balkans after Lepanto and Venice’s struggle to maintain long lasting peace with the Ottomans (1573-1645) - Ardian Muhaj (Tarih Dergisi)
The sixteenth century was a time when projects against Ottoman power were diminishing. This sixteenth century trend changed dramatically after the battle of Lepanto on 7 October 1571, when the Holy League coalition forces inflicted a significant defeat on the Ottoman fleet. This study investigates how Venice responded to the growing anti-Ottoman projects and movements in the Balkans in order to keep a long lasting peace with the Ottomans that characterized the period from the peace treaty between Venice and the Ottoman Empire in 1573 until the war of Crete in 1644. Venice’s struggle for peace in this period, was of crucial importance in the relatively quiet situation in Rumelia during this period compared to the disquiet and social unrest that characterized Anatolia, especially during the Celali revolts.